Keintransitifan Terbelah dalam Bahasa Arab - Az-Zahra, Namira; Mulyadi, Mulyadi (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2025)
The phenomenon of split-intransitivity divides intransitive verbs into two types, namely unergative and unaccusative which differ in syntactic structure and semantic role. As a complex language and rich in morphological systems, Arabic does not explicitly distinguish between the two verbs. So this research is conducted to find out the split ditransitive especially unergative verbs and unaccusative verbs found in Arabic. This research is a qualitative research. Data in the form of sentences that use unergative and unaccusative verbs in Arabic, collected through documentation studies from the third edition of the book Arabic Verbs and Essential Grammar and related scientific journals, then analyzed using the agih method with direct element division and form change techniques. The result of the research is that unergative verbs (al-af‘āl al-lāzimah) in Arabic include various categories, namely character verbs, instinct verbs, behavior verbs, color verbs, physical and emotional state verbs, and verbs with fa’ula patterns. While unaccusative verbs (al-af‘āl al-muṭāwa‘ah) include various patterns such as the transition of object to subject without any change in verb form, passive construction and morphosyntactic affixation process.Keywords – Arabic, Split Intransitivity, Unaccusative, Unergative